2011
DOI: 10.1021/jo201781x
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Friedel–Crafts Alkylation of Hydronaphthalenes

Abstract: An efficient and versatile synthesis of chiral tetralins has been developed using both inter- and intramolecular Friedel-Crafts alkylation as a key step. The readily available hydronaphthalene substrates were prepared via a highly enantioselective metal-catalyzed ring opening of meso-oxabicyclic alkenes followed by hydrogenation. A wide variety of complex tetracyclic compounds have been isolated with high levels of regio-, diastereo-, and enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…The obsereved cis -diastereoselectivity in this work is consistent with the reported synthesis of related-tetracyclic molecules via Friedel–Crafts cyclization (Scheme 2, lower panel) promoted by metal-based Lewis acids [2728]. Noteably, none of the synthesized molecules described in these two reports contains an angular –OH group.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The obsereved cis -diastereoselectivity in this work is consistent with the reported synthesis of related-tetracyclic molecules via Friedel–Crafts cyclization (Scheme 2, lower panel) promoted by metal-based Lewis acids [2728]. Noteably, none of the synthesized molecules described in these two reports contains an angular –OH group.…”
Section: Resultssupporting
confidence: 91%
“…Thus, we were concerned about the possibility of getting a mixture of 5 and 9 under the planned IFCEA cyclization of 6 . However, a literature survey indicated that cis -diastereoselective synthesis of related tetracyclic molecules via intramolecular Friedel–Crafts cyclization of tetralins (Scheme 2, lower panel) has been described by Lautens and co-workers [2728]. …”
Section: Resultsmentioning
confidence: 99%
“…Among the various catalysts investigated at 5 mol-% (Table 1, Entries 1-6), Sn(OTf) 2 , Al(OTf) 3 and Fe(OTf) 3 catalysed the intramolecular reaction of 1a in moderate yields (Table 1, entries 1-3). Sc(OTf) 3 , In(OTf) 3 and Bi(OTf) 3 were the most efficient catalysts (Table 1, Entries 4-6) and led to the expected bicyclic structure 2a in yields of 92-96 %.…”
Section: Catalyst Screeningmentioning
confidence: 99%
“…Some selected examples are presented in Scheme 1, including celestolide, a commercial perfume component with an outstanding musk odour, [1] lasofoxifene for the treatment of osteoporosis, the anticancer agent podophyllotoxin [2] and the antifertility agent trans-1- (2-{4-[6,7,8,9-1 variety of polycyclic compounds have been isolated in high yields. Lactonisation could be observed for esters with 2,2-disubstituted terminal olefins through a Lewis acid catalysed reaction between the olefin and one of the ester groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation